2018
DOI: 10.1016/j.vaccine.2018.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, believes, determinants and organisational barriers behind the low seasonal influenza vaccination uptake in healthcare workers – A cross-sectional survey

Abstract: There is a need for guidance for the organization of seasonal influenza campaigns, in which education, communication and easy accessible vaccination are promoted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
104
2
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(125 citation statements)
references
References 35 publications
16
104
2
3
Order By: Relevance
“…Our study reported that influenza vaccination uptake of HCWs was significantly associated with workplace requirement (PR = 3.21, 95% CI: 2.48-4.04) or promotion for influenza vaccination (PR = 1.75, 95% CI: 1.43-2.14) by workplace. This result was in accordance with previous studies [19]. As mentioned above, combining workplace requirement and free policy seems to be the most effective method for improving influenza vaccination coverage in HCWs.…”
Section: Discussionsupporting
confidence: 93%
“…Our study reported that influenza vaccination uptake of HCWs was significantly associated with workplace requirement (PR = 3.21, 95% CI: 2.48-4.04) or promotion for influenza vaccination (PR = 1.75, 95% CI: 1.43-2.14) by workplace. This result was in accordance with previous studies [19]. As mentioned above, combining workplace requirement and free policy seems to be the most effective method for improving influenza vaccination coverage in HCWs.…”
Section: Discussionsupporting
confidence: 93%
“…The low RR recorded in this study seems to indicate that staff vaccination is a critical issue that needs to be carefully addressed, focusing specifically on the context of NHs. Similar studies exploring NH staff perceptions of flu vaccination throughout a survey found comparable response rates (e.g., from 10% to 45%), confirming the complexity of the topic [13][14][15][16]. This evidence is further underlined by the reported extremely low adherence to annual flu vaccination.…”
Section: Discussionsupporting
confidence: 66%
“…Despite almost 10 years of efforts and extensive campaigns to vaccinate health care professionals in most European countries, vaccination coverage is still low in this group [20]. In own study, the percentage of vaccinated persons was similar to Italian studies, but considerably lower than in other countries, such as the United States (90.5%), the United Kingdom (68.7%), and other European countries (40%-45%) [20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 67%